Evaluasi Kinerja Apill dan Geometrik Simpang 3 Sungai Bengkel Kota Bengkalis - Nursafika Syafika; Muhammad Idham (Jurnal Ilmiah Rekayasa Sipil, 2021)
Third junction of Sungai Bengkel was a Signalized Intersection which a hasn’t have traffic jam ,which has three approach, are North approach, West approach and East approach. However, the alinyemen for the North approach has problems that make it difficult for vehicles, especially four-wheelers to turn because the effect bottle neck resulting in the slow motion of the vehicle and change of phase time . the problem solving, the evalution of traffic light and intersection geometry were carried out by widening the alinyemen for the North approach and East approaches and doing changes in cycle time. The purpose of evaluating the performance of traffic light and Geometrics at the third intersection of Sungai Bengkel is to determine the value of the degree of saturation and to know the performance of the intersection.At the intersection planning, it refers to the PKJI 2014 for Intersection Performance, while for the Geometrics it refers to Module 4 of the Ministry of Public Works and Public Housing on Geometric Planning of Plane Intersections.Based on the calculation results of the Sungai Bengkel junction performance indicate that, the degree of saturation < 0.85,which is 0.529 for North, 0.537 for East, and 0.570 for West .With the radius is 15 m, and the cycle time of traffic light 50 second, with the delay time as long as 17 second/pcu